2020
DOI: 10.3390/ijerph17041345
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and Prostate Cancer: An Updated Systematic Review and Meta-Analysis

Abstract: The International Agency of Research in Cancer (IARC) has recently confirmed shift work as a type 2A carcinogen. The results presented in published epidemiological studies regarding prostate cancer are inconsistent and the association remains controversial. The aims of this study were: (a) to investigate the possible association between shift work and prostate cancer incidence, identifying possible sources of heterogeneity; and (b) to analyze the potential effect of publication bias. A search for cohort and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Recent meta-analyses evaluating occupational exposure proposed asbestos, organochlorine pesticides, chromium, and shift work as risk factors for PCa incidence [7,64,65]. Conversely, these studies were unable to show an association between rotating/night shift work and PCa [66]. A wide variety of dietary factors have been proposed to be associated with the risk of overall and aggressive PCa.…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%
“…Recent meta-analyses evaluating occupational exposure proposed asbestos, organochlorine pesticides, chromium, and shift work as risk factors for PCa incidence [7,64,65]. Conversely, these studies were unable to show an association between rotating/night shift work and PCa [66]. A wide variety of dietary factors have been proposed to be associated with the risk of overall and aggressive PCa.…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%
“…It was noted that studies with lower population samples were of 'fair' quality and also reported higher incidence rates than the 'good' quality study. This phenomenon of likelihood of publishing studies with lower sample sizes and positive associations has been previously described by researchers [70]. Additionally, studies with fair quality were also older (published in the 1990s) than the 'good' quality study (published in 2003) [25].…”
Section: Other Considerationsmentioning
confidence: 61%
“…16,17 However, this stands in contrast with the most recent systematic reviews and meta-analyses, in which no associations were found between night shift work and prostate cancer. 14,15 Based on autopsy findings, prostate cancers may have latency times of up to 15-20 years, the estimated time period from the first malignant transformation of cells to clinical diagnosis. 36 The effect estimates in our analysis indicated that the hazard of aggressive prostate cancer is not affected by 10, 15 and 20 years of f Cox regression adapted to a case cohort design with age as the time scale.…”
Section: Discussionmentioning
confidence: 99%
“…6 The International Agency for Research on Cancer (IARC) recently reconfirmed its classification of night shift work as a probable human carcinogen (group 2A), with limited positive evidence for prostate cancer. 6 Individual studies [7][8][9][10][11][12][13] as well as systematic reviews and meta-analyses 14,15 have shown inconsistent results, although positive associations have been found for aggressive prostate cancer and longer durations of night shift work exposure. 10,11 A positive association with prostate cancer has also been found in relation to rotating shift work (day and night shift rotation).…”
Section: Introductionmentioning
confidence: 99%